2020
DOI: 10.1038/s41598-020-59609-9
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-Occlusion of the Internal Carotid Artery in Acute Ischemic Stroke: Clinical Outcome after Mechanical Thrombectomy

Abstract: pseudo-occlusion (po) of the cervical internal carotid artery (cicA) can be caused by distal icA occlusion.We explored the clinical impact of po after mechanical thrombectomy (Mt). patients who underwent MT to treat distal ICA occlusions between July 2012 and March 2018 were reviewed. A cICA-PO was defined as when single phase computed tomography angiography (CTA) revealed a gradual decline in contrast above the level of the carotid bulb. We investigated the relationship between a cicA-po and outcome; we also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…They suggested that intraoperative exploration using the microcatheter should be the best way to diagnose the occlusion location and further confirm the presence of PO. Previous studies reported the incidence of PO to be 11–56.3% as confirmed by DSA ( 5 , 6 , 10 , 11 ). The prevalence of PO in our series was in line with the findings in the research above.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…They suggested that intraoperative exploration using the microcatheter should be the best way to diagnose the occlusion location and further confirm the presence of PO. Previous studies reported the incidence of PO to be 11–56.3% as confirmed by DSA ( 5 , 6 , 10 , 11 ). The prevalence of PO in our series was in line with the findings in the research above.…”
Section: Discussionmentioning
confidence: 78%
“…It has been accepted that successful revascularization is an important determinant of good outcome in patients with acute ischemic stroke ( 17 ). Two recent studies showed that patients with PO were more likely to have lower recanalization rates (65.0–71.4%) than those without PO (90.3–100.0%) after thrombectomy ( 10 , 11 ). Likewise, Chen et al ( 9 ) reported a lower recanalization rate of 36.8% in PO patients compared with non-PO patients (62.7%) after the treatment of intravenous thrombolysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, all patients with pseudo-occlusion had a progressive gradual decrease of contrast in the cervical ICA on CTA, with apparent patency of the bulb. This finding is secondary to the combination of contrast with retained blood; it receives different terms in the scientific literature, being ‘flame-shaped’ occlusion the most used [7] , [9] , [10] , [18] , [19] , [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Between 45% and 67% of intracranial ICA occlusions, cervical ICA is non-opacified in CTA. This finding is caused by slow arterial flow and can simulate an extracranial occlusion (pseudo-occlusion) [7] , [8] , [9] , [10] . The location and extent of the thrombus concerning anterior choroidea, posterior communicating and ophthalmic arteries could explain the presence of this radiological sign.…”
Section: Introductionmentioning
confidence: 97%